The Integration of HR Analytics and Decision Making - Muktamar, Ahmad; Nurnaningsih A (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Integrating HR Analytics into organizational decision-making processes is crucial for modern businesses looking to improve human resource management practices and drive better decision-making outcomes. This systematic literature review explores the importance of HR Analytics integration, its key determinants, and its impact on organizational performance and decision-making effectiveness. Through an analysis of existing literature, this review identifies factors that influence HR Analytics integration, such as data collection practices, technology availability, managerial skills, and organizational policies. This review also revealed a research gap regarding the optimal use of HR Analytics for strategic decision making, highlighting the need for further research in this area. Overall, these findings underscore the importance of HR Analytics in driving better HR management practices and better organizational decision-making outcomes.